Pressing issues in education - a discussion - Biseth, Heidi; Holmarsdottir, Halla (Nordic Journal of Comparative and International Education (NJCIE), 2021)
Editorial discussion in an audio file - available for download on the right-hand side column - 7,5 minutes.